2022
DOI: 10.1002/mop.33364
|View full text |Cite
|
Sign up to set email alerts
|

The gain and noise figure comparison of single‐pass, double‐pass, and dual‐stage triple‐pass thulium‐doped fiber amplifiers in S‐band with thulium‐doped fiber optimization

Abstract: This study presents a comparison of three different S-band thulium-doped fiber amplifiers (TDFA) designs. The gain performances of the amplifiers are analyzed based on each scheme, separately. With −20 dBm input power, to provide ground-state and excited-state absorptions, the 1050 nm pump is used in all designs. The thulium-doped fiber (TDF) lengths are optimized for maximum gain by using the single parameter single result optimization of Optisystem 18.0 software. A reflector is integrated into the double-pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…In addition, in some research, the gain has been increased by adding a mirror or an optical circulator to the basic TDFA design with double-pass con gurations [27][28][29][30][31]. In some of them, these designs are called double-pass; in others, they are called double-stage [30][31].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, in some research, the gain has been increased by adding a mirror or an optical circulator to the basic TDFA design with double-pass con gurations [27][28][29][30][31]. In some of them, these designs are called double-pass; in others, they are called double-stage [30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Harun et al used and compared two types of two-stage triple-pass EDFAs [34]. On the other hand, considering the S-band, no study has been done on the TP-TDFA other than the research we have done before [30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that dual-stage triple-pass TDFA offers the optimal design. 17 Yigit et al proposed a three-stage six-pass EDFA as a preamplifier and its performance was analyzed after optimizing various design parameters. 18 To further elaborate on the literature survey, the above discussed past studies related to HDFAs have been summarized in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Murat et al compared different S‐band TDFA designs considering the performance metrics of gain and NF. They found that dual‐stage triple‐pass TDFA offers the optimal design 17 . Yigit et al proposed a three‐stage six‐pass EDFA as a preamplifier and its performance was analyzed after optimizing various design parameters 18 .…”
Section: Introductionmentioning
confidence: 99%